2010
DOI: 10.1104/pp.110.167007
|View full text |Cite
|
Sign up to set email alerts
|

ThePopulusClass III HD ZIP,popREVOLUTA, Influences Cambium Initiation and Patterning of Woody Stems    

Abstract: The secondary growth of a woody stem requires the formation of a vascular cambium at an appropriate position and proper patterning of the vascular tissues derived from the cambium. Class III homeodomain-leucine zipper (HD ZIP) transcription factors have been implicated in polarity determination and patterning in lateral organs and primary vascular tissues and in the initiation and function of shoot apical meristems. We report here the functional characterization of a Populus class III HD ZIP gene, popREVOLUTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
126
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 57 publications
4
126
0
2
Order By: Relevance
“…Among many SNP-trait associations, these studies revealed genetic associations of wood cellulose content and leaf phenology traits with SNPs in noncoding regions of distinct splice variants of the poplar REV gene Potri.009G014500 (PtREV; Fig. 1; Table I), consistent with fundamental functions for REV in regulating the architecture of leaf and vascular systems (Zhong et al, 1997;Otsuga et al, 2001;Emery et al, 2003;Robischon et al, 2011;Stirnberg et al, 2012). An additional putatively functional polymorphism common to all splice variants of REV is associated with Melampsora spp.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Among many SNP-trait associations, these studies revealed genetic associations of wood cellulose content and leaf phenology traits with SNPs in noncoding regions of distinct splice variants of the poplar REV gene Potri.009G014500 (PtREV; Fig. 1; Table I), consistent with fundamental functions for REV in regulating the architecture of leaf and vascular systems (Zhong et al, 1997;Otsuga et al, 2001;Emery et al, 2003;Robischon et al, 2011;Stirnberg et al, 2012). An additional putatively functional polymorphism common to all splice variants of REV is associated with Melampsora spp.…”
Section: Resultsmentioning
confidence: 93%
“…In particular, REV (synonymous with INTERFASCICULAR FBERLESS1 and AMPHIVASAL VASCULAR BUNDLES1 [AVB1]), encoding one of five Arabidopsis (Arabidopsis thaliana) class III HD ZIP transcription factors, regulates meristem function, polarity of lateral organs, vascular architecture and development, and interfascicular fiber differentiation in Arabidopsis and other angiosperms Ratcliffe et al, 2000, Emery et al, 2003Zhong and Ye, 2004). In poplar, the REV ortholog PtREV influences cambium initiation and patterning of woody stems (Robischon et al, 2011;Hu et al, 2012). REV is part of a complex regulatory system involving auxin, KANADI (KAN1) transcription factors, and miRNA (Emery et al, 2003;Ilegems et al, 2010;Brandt et al, 2012;Schuetz et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study using Acacia mangium as lignification model system, the conserved miR166 was shown to be strongly down-regulated in xylem when compared to phloem, suggesting its potential role in xylem development by indirect regulation of the genes involved in lignin biosynthesis (Ong and Wickneswari 2012). Transgenic Populus expressing a miR166 resistant target gene have developed phenotypic abnormalities affecting the primary and secondary growth, including the abnormal formation of cambia within cortical parenchyma that can produce secondary vascular tissues in reverse polarity (Robischon et al 2011). More recently, Puzey et al (2012) identified several xylem-enriched miRNAs predicted to target genes known to be important in secondary growth, including xyloglucan endotransglycosylase/hydrolase and vascular-related transcription factors (Puzey et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have explored the potential impact of miRNAs during the growth of longlived perennial plants (Robischon et al, 2011;Lu et al, 2013). Recently, several studies have used reverse genetics on woody plants to reveal the biological importance of miRNA-target interactions in tree growth and wood formation (Robischon et al, 2011;Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%